2020
DOI: 10.3390/antiox9020161
|View full text |Cite
|
Sign up to set email alerts
|

CsCYT75B1, a Citrus CYTOCHROME P450 Gene, Is Involved in Accumulation of Antioxidant Flavonoids and Induces Drought Tolerance in Transgenic Arabidopsis

Abstract: CYTOCHROME P450s genes are a large gene family in the plant kingdom. Our earlier transcriptome data revealed that a CYTOCHROME P450 gene of Citrus sinensis (CsCYT75B1) was associated with flavonoid metabolism and was highly induced after drought stress. Here, we characterized the function of CsCYT75B1 in drought tolerance by overexpressing it in Arabidopsis thaliana. Our results demonstrated that the overexpression of the CsCYT75B1 gene significantly enhanced the total flavonoid contents with increased antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 66 publications
0
65
0
1
Order By: Relevance
“…Gao et al (2020) also showed that drought stress promoted the accumulation of secondary metabolites such as flavonoids in two Adonis species, which in turn reduced H 2 O 2 content and promoted drought resistance. Recently, a P450 gene, CsCYT75B1 from Citrus CYTOCHROME, was positively linked to flavonoids and drought resistance (Rao et al 2020). In this study, our transcriptome analysis revealed that the expression of some key genes involved in flavonoid biosynthesis showed significant differences between B73 and doi57 before and after drought treatment ( Fig.…”
Section: Discussionmentioning
confidence: 54%
“…Gao et al (2020) also showed that drought stress promoted the accumulation of secondary metabolites such as flavonoids in two Adonis species, which in turn reduced H 2 O 2 content and promoted drought resistance. Recently, a P450 gene, CsCYT75B1 from Citrus CYTOCHROME, was positively linked to flavonoids and drought resistance (Rao et al 2020). In this study, our transcriptome analysis revealed that the expression of some key genes involved in flavonoid biosynthesis showed significant differences between B73 and doi57 before and after drought treatment ( Fig.…”
Section: Discussionmentioning
confidence: 54%
“…Remy et al (2013) identified that an MFS member ZIFL1 modulates drought tolerance by regulating stomatal closure in Arabidopsis . Moreover, P450 genes are essential for the phytohormones homeostasis and the biosynthesis of different varieties of metabolites, and that drought triggered the activation of P450 genes and flavonoid accumulation (Rao, Xu, Tang, et al, 2020; Zandalinas, Sales, Beltrán, Gómez‐Cadenas, & Arbona, 2017). Our results suggested that ZmNST3 may improve drought resistance through enhancing the expression of those genes under drought stress.…”
Section: Discussionmentioning
confidence: 99%
“…(2020) 26 CitPH1 and CitPH5 Sour lemon, orange, pummelo, and rangpur lime fruits Anthocyanin and flavor Strazzer et al. (2019) 27 CsCYP75B1 Sweet orange A. thaliana Flavonoid biosynthesis Rao et al. (2020) 28 CsUDP78D3 Sweet orange A. thaliana Anthocyanin Rao et al.…”
Section: Key Genes Associated With Citrus Domestication and Their Impmentioning
confidence: 99%